COMPERATIVE STUDY OF WOODS TYPE TO THE SMOKED CATFISH (Pangasius hypopthalmus) FLAVOUR - Yuliandri, Ade; ', Syahrul; ', Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate the quality of smoked catfish smoked withdifferent types of woods. The fish weighing 250-300gr each were smoked with hot andliquid smoking method using rambutan wood (Nephelium lappacium) and medang wood(Dcinamouns spp). The smoked catfishes were evaluated for sensory quality, moisture, fenolvalue, acid value and pH. The smoked catfishes which were smoked with rambutan woodwere compared to that smoked with medang wood. The results showed that the smokedcatfishes which were smoked with rambutan wood had a better quality than that medangwood. Moisture, fenol value, acid value and pH of smoked catfishes which were smokedwith rambutan wood was 16,52%, 2,51%, 4,18% and 6,1% respectively, and that smokedwith medang wood was 18,31%, 2,17%, 4,10% and 6,33% respectively.Kunci : smoked catfish (Pangasius hypopthalmus) , sensory quality.